Pengaruh Pandemi Covid-19 Terhadap Profitabilitas Perusahaan Industri Barang Konsumsi Subsektor Makanan & Minuman, Kosmetik & Rumah Tangga, Dan Obat-Obatan Yang Terdaftar Di Bursa Efek Indonesia - Alicia Mulianto; Kelly Wijaya; Yulius Jogi (Business Accounting Review, 2020)
The COVID-19 pandemic has various impacts on companies and the country's economy. In Indonesia, there have been many bankruptcies and layoffs that have caused losses to companies. In the midst of a pandemic, there is a panic buying phenomenon, which is a change in people's shopping behavior where people buy products with more quantities than their normal spending. During the pandemic, people also tend to save expenses and prioritize household spending, which is considered to have a positive impact on the profitability of consumer goods industrial companies in Indonesia. The purpose of this research is to find out the impact of the COVID-19 pandemic on company profitability. The object of this research is 30 consumer goods industry companies listed on the Indonesia Stock Exchange in 2019-2020 which were selected by purposive sampling method. Data were analyzed using multiple linear regression analysis. Based on the results of the analysis, it was found that the COVID-19 pandemic did not have a positive effect but a negative and significant effect on profitability where the company's profitability actually decreased during the pandemic. Meanwhile, firm size and market share were found to have no significant effect on profitability.